2017
DOI: 10.1016/j.beproc.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Does previous use affect litter box appeal in multi-cat households?

Abstract: It is commonly assumed that cats actively avoid eliminated materials (especially in multi-cat homes), suggesting regular litter box cleaning as the best defense against out-of-box elimination. The relationship between previous use and litter box appeal to familiar subsequent users is currently unknown. The purpose of this study was to investigate the relationship between previous litter box use and the identity of the previous user, type of elimination, odor, and presence of physical/visual obstructions in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
0
19
1
Order By: Relevance
“…One study reported the relationship between urine and faecal odour and litter box preferences 34 . However, another study demonstrated that cats were not averse to sharing a litter box 35 . The maintenance of litter boxes is the most important factor, especially in multicat households.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported the relationship between urine and faecal odour and litter box preferences 34 . However, another study demonstrated that cats were not averse to sharing a litter box 35 . The maintenance of litter boxes is the most important factor, especially in multicat households.…”
Section: Discussionmentioning
confidence: 98%
“…It is suggested that such risks can be mitigated by the use of a microchip controlled cat flap ( 46, 47 ), but there are currently no scientific data to support this. Allowing some access to the outside might increase opportunities to eliminate in general (via access to outside latrines) and thus reduce the risk that litter boxes in the home become unacceptable to the cat, perhaps because of the presence of faeces in it ( 20 ), as they are being used less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Without good scientific data, ideological associations may inadvertently be believed to be genuine risk factors. For example, Ellis et al ( 20 ) investigated the influence of previous litter box use on its reuse and found through careful experimental manipulation that it was not the odor of another cat's urine or faeces in the litter that was avoided by cats (obvious association for a macrosmatic species like the cat), but the physical/visual presence of a wet patch or object looking like a faecal deposit which mattered. This work highlights the importance of original research which challenges conventional wisdom on this topic and the danger of uncritically accepting the opinion of others without good data.…”
Section: Introductionmentioning
confidence: 99%
“…The study design itself did assist in reducing the chances of resource guarding in the room by having multiple water bowls, toys, climbing structures, and enough litter boxes for each cat. While each cohort was acclimated to the room for at least two weeks to allow the cats to become accustomed to each other and establish a hierarchy, multi-cat interactions can be a complicated process of events and can add additional stress to the cats, resulting in changes in behaviour [27,28,29]. This also could have potentially led to variations in cat elimination behaviour due to aggressor cats guarding the litter box area [29].…”
Section: Discussionmentioning
confidence: 99%
“…While each cohort was acclimated to the room for at least two weeks to allow the cats to become accustomed to each other and establish a hierarchy, multi-cat interactions can be a complicated process of events and can add additional stress to the cats, resulting in changes in behaviour [27,28,29]. This also could have potentially led to variations in cat elimination behaviour due to aggressor cats guarding the litter box area [29]. We also observed that the cats had a positional preference for litter boxes, with the most favoured position being against a wall so that they can watch their surroundings at the same time as using the litter box [30].…”
Section: Discussionmentioning
confidence: 99%